Pengaruh Kompensasi dan Motivasi Kerja terhadap Kinerja Karyawan Outsourcing pada PT Catur Mulia Mandiri - Muhammad Lukman Hadi; Komarun Zaman; Syamsul Arifin (Pustaka Digital Indonesia, 2026)
This research is urgent given the increasing reliance on outsourcing employees in competitive industries, where optimizing performance through appropriate compensation and motivation strategies becomes essential for sustaining organizational productivity and stability. Employee performance is a critical determinant of organizational success. This study aims to analyze the effect of compensation and work motivation, both partially and simultaneously, on the performance of outsourcing employees at PT Catur Mulia Mandiri, Sidoarjo. This research uses a quantitative approach with a survey method. The population in this study were all 511 employees of PT Catur Mulia Mandiri placed at PT Surya Pertiwi Nusantara. The sample was determined using the Slovin formula with a margin of error of 10%, resulting in 100 respondents selected by simple random sampling. Data were collected through questionnaires and analyzed using multiple linear regression analysis with the help of SPSS version 25. The results showed that: (1) Compensation has a positive and significant effect on employee performance, (2) Work motivation has a positive and significant effect on employee performance, and (3) Compensation and work motivation simultaneously have a positive and significant effect on employee performance with a contribution of 59.4%. These findings indicate that improving compensation schemes and strengthening work motivation are key strategies for enhancing the performance of outsourcing employees.